Effects of storm clustering on beach/dune evolution - Harshinie Karunarathna (Marine Geology, 2015)
Impacts of storm clustering on beach/dune morphodynamics were investigated by applying the state-of-the-art numerical model XBeach to Formby Point (Sefton coast, UK). The adopted storm cluster was established by analysing the observed winter storms from December 2013 to January 2014 using a storm threshold wave height. The first storm that occurred during this period is regarded as exceptionally intense, and the occurrence of such a cluster of events is very unusual. A 1D model was setup for the highly dynamic cross-shore at Formby Point. After initial calibration of the model parameters against available post-storm profile data, the model was used for the simulation of the storm cluster. It was assumed that no beach recovery occurred between adjacent storms due to the very short time intervals between storms. As a result, the final predicted post-storm profile of the previous storm was used as the pre-storm profile of the subsequent storm. The predicted evolution during each storm was influenced by the previous storms in the cluster. Due to the clustering effect, the bed level change is not proportional to the storm power of events within the cluster, as it would be in an individual storm case. Initially, the large storm events interact with the multi-bared foreshore enabling the subsequent weaker storms to influence the upper beach and lower dune system. This results in greater change at the dune toe level also during less severe subsequent storms. It is also shown that the usual water level threshold used to define dune erosion is over predicted by about 1 m for extreme storm conditions. The predicted profile evolution provides useful insights into the morphodynamic processes of beach/dune systems during a storm cluster (using Formby Point as an example), which is very useful for quantifying the clustering effects to develop tools for coastal management.